Impact of genetically modified herbicide-resistant maize on rhizosphere bacterial communities - Ye-Jin Jang; Sung-Dug Oh; Joon Ki Hong; Jong-Chan Park; Seong-Kon Lee; Ancheol Chang; Doh-Won Yun; Bumkyu Lee (GM Crops & Food)
Rhizosphere bacterial community studies offer valuable insights into the environmental implications of genetically modified (GM) crops. This study compared the effects of a non-GM maize cultivar, namely Hi-IIA, with those of a herbicide-resistant maize cultivar containing the phosphinothricin N-acetyltransferase gene on the rhizosphere bacterial community across growth stages. 16s rRNA amplicon sequencing and data analysis tools revealed no significant differences in bacterial community composition or diversity between the cultivars. Principal component analysis revealed that differences in community structure were driven by plant growth stages rather than plant type. Polymerase chain reaction analysis was conducted to examine the potential horizontal transfer of the introduced gene from the GM maize to rhizosphere microorganisms; however, the introduced gene was not detected in the soil genomic DNA. Overall, the environmental impact of GM maize, particularly on soil microorganisms, is negligible, and the cultivation of GM maize does not alter significantly the rhizosphere bacterial community.